2012
DOI: 10.3389/fpls.2012.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Spliceosome-Activating Complex: Molecular Mechanisms Underlying the Function of a Pleiotropic Regulator

Abstract: Correct interpretation of the coding capacity of RNA polymerase II transcribed eukaryotic genes is determined by the recognition and removal of intronic sequences of pre-mRNAs by the spliceosome. Our current knowledge on dynamic assembly and subunit interactions of the spliceosome mostly derived from the characterization of yeast, Drosophila, and human spliceosomal complexes formed on model pre-mRNA templates in cell extracts. In addition to sequential structural rearrangements catalyzed by ATP-dependent DExH/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 154 publications
(198 reference statements)
1
112
0
Order By: Relevance
“…Intriguingly, among the proteins that interact with Prp8, our MS results identified a set of splicing factors, which form the Prp19 complex (Prp19C), also known as NTC (21,31,32). Compared with Col, the atprmt5 mutants showed significantly reduced normalized spectral counts from the Prp19C/NTC core proteins, including MAC3A and MAC3B (human Prp19 homolog in Arabidopsis), MOS4 (human SPF27 homolog in Arabidopsis), CDC5, and PRL1, and the Prp19C/NTC-associated proteins (SYF1, AQR, CRN1c, SKIP, ECM2, ISY1, and PPI) (Fig.…”
Section: The Suppressors Partially Rescue the Splicing Alterations Ofmentioning
confidence: 99%
“…Intriguingly, among the proteins that interact with Prp8, our MS results identified a set of splicing factors, which form the Prp19 complex (Prp19C), also known as NTC (21,31,32). Compared with Col, the atprmt5 mutants showed significantly reduced normalized spectral counts from the Prp19C/NTC core proteins, including MAC3A and MAC3B (human Prp19 homolog in Arabidopsis), MOS4 (human SPF27 homolog in Arabidopsis), CDC5, and PRL1, and the Prp19C/NTC-associated proteins (SYF1, AQR, CRN1c, SKIP, ECM2, ISY1, and PPI) (Fig.…”
Section: The Suppressors Partially Rescue the Splicing Alterations Ofmentioning
confidence: 99%
“…To identify connections between the circadian clock and AS in plants, we investigated which splicing factors were clock-regulated (24)(25)(26). We found 83 splicing-related genes that cycle at the mRNA level, and thus represent candidate regulators of clock-mediated AS (Dataset S1).…”
Section: Resultsmentioning
confidence: 99%
“…CRK5 (called alternatively PIP-D) was originally identified in yeast two-hybrid and in vitro protein binding assays as a potential interaction partner of the C-terminal WD40-repeat domain of nuclear PRL1 protein, a subunit of the spliceosome-activating complex (Németh et al, 1998;Koncz et al, 2012). Although subsequent studies did not confirm in vivo formation of a CRK5-PRL1 complex under normal growth conditions, we found that inactivation of the CRK5 gene by a T-DNA insertion in the MPIZ mutant line 38225 (crk5-1; Ríos et al, 2002; see Supplemental Figure 1A online) resulted in reduced primary root elongation ( Figure 1A), analogously to the prl1 mutation (Németh et al, 1998).…”
Section: Inactivation Of Crk5 Results In Delayed Gravitropic Responsesmentioning
confidence: 99%